War-Induced Energy Commodity Price Dynamics : Index Design and Impact Assessment - Gupta, Nupur; Sachdeva, Jagdish Kumar; Mishra, Akshay Kumar (Indian Journal of Finance, 2024)
Purpose : We analyzed the impact of three wars—the Gulf War of 1990–91, the US Invasion of Iraq (2003–2011), and the ongoing Russian invasion of Ukraine (from 2022 onwards)—on energy commodities and used the findings to predict the effect of wars on energy commodities during the ongoing Russia-Ukraine war. Research Methodology : We employed a novel approach to determining the energy commodity index using equal risk contribution methodology. This index was called the War Energy Commodity Index. It was constructed using monthly prices of six energy commodities—natural gas, Brent Crude, WTI crude, gas oil, heating oil, and RBOB Gasoline—from June 1990 to July 2024. We employed a regression model to assess the impact of the three wars on the War Energy Commodity index using dummy variables for the different war periods and their lagged values. Findings : The findings indicated that while war-triggered volatility initially affected prices, indices tended to return to their original levels post-war, with only long-term wars demonstrating statistically significant impacts on energy commodity prices. Practical Implications : Predicting energy commodity prices would be helpful to industry practitioners. Our study encouraged economic agents to invest in commodity indices based on equal risk contribution and index providers to launch an index based on this methodology. Originality/Value : The index constructed in this paper distributed risk equally among the six energy commodities. To our knowledge, no energy index of this kind has been created. The index provides a predictive model for the Russia-Ukraine warfare.